Euphotic Depth Zone Variation in Peninsular Malaysia Maritime - Asmala, A.; Abd Rahman, Mat Amin; Fadhli , Ahmad; Mustafa, Mamat; Khiruddin, Abdullah (HIKARI LTD, 2014)
This study is conducted in Peninsular Malaysia maritime to investigate the euphotic zone depth (Zeu) variation and the possible suspended matter that may contribute to the variation. The Zeu data were acquired from the MODIS Aqua satellite from November 2002 to September 2013. The result shows that the Zeu along the Malaysia maritime are highly seasonal-dependent. The lowest Zeu values are observed during the northeast monsoon season (NEMS) in the east coast Peninsular Malaysia and during the southwest monsoon season (SWMS) for the west coast area. Chlorophyll- a (Chl-a) and colored dissolved organic matter (CDOM) are found to be the contributing factors for the coastal line and open water area. While, sediment only contributes to the area located along the coastal line where lower Zeu values are observed.